Atmospheric corrosion of carbon and galvanized steel under high rainfall conditions - Ariel Arroyo Heredia; Hector David Agudelo Arias; Maycol F. Mena; Elcy Serna Copete; F.A. Vásquez; Nerly Liliana Mosquera; Edison Banguero Palacios; Reiner Palomino Lemus; J.A. Calderón; Samir Córdoba Machado (Heliyon)
The corrosion rates of carbon steel and galvanized steel according to the ISO 9223 standard, the effect of pollutant contamination and atmospheric aggressiveness under high rainfall conditions in the Chocó department were studied. Carbon and galvanized steel samples, chloride, and sulfur collectors were exposed in three atmospheric stations in three strategic positions covering the Colombian Pacific: Quibdó, Andagoya and Bahía Solano, for different exposure periods (up to 18 months). The structural-micro characterization of corrosion products was evaluated via X-ray diffraction (XRD), Raman spectroscopy and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy SEM-EDS. The results indicate that all study regions obtained the highest time of wetness category (τ5). The sulfur-containing pollution (SO2) was categorized as P0 (rural atmosphere) with average values of Pd ≤ 4 mg/m2 - day. Bahia Solano station showed the highest chloride deposition rate, reporting an average of 8.3 mg/m2-day (categorized as δ1), according to ISO 9223. Due to the extremely high rainfall in the department of Chocó, the results initially suggested hematite formation on carbon steel. After several months, there was a phase transition to lepidocrocite (γ-FeOOH). The formation of γ-FeOOH induces active corrosion on the iron substrate. The zincite phase (ZnO) was observed in the galvanized steel corrosion products. The corrosion rates of carbon and galvanized steel in the location of Quibdó-Colombia were higher than in previous reports. Data analysis reveals that the precipitation variable, which governs the TOW and pollution contaminants, significantly influences the corrosion of these exposed metals.